2020
DOI: 10.7150/jca.37890
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor functions and mechanisms of nitidine chloride in human cancers

Abstract: Nitidine chloride (NC), a quaternary ammonium alkaloid, exhibits multiple biological activities, including antimalarial, antifungal, and antiangiogenesis. Recently, NC has been characterized to perform antitumor activity in a variety of malignancies. NC has been identified to suppress cell proliferation, stimulate apoptosis, and induce cell cycle arrest, retard migration, invasion and metastasis. Moreover, NC is reported to sensitize cancer cells to chemotherapeutic drugs. In this review article, we describe t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 62 publications
2
32
0
1
Order By: Relevance
“…One of the key advantages of using natural products instead of synthetic compounds in drug discovery is that natural products are likely to be multi-target compounds. Nitidine is a common alkaloid found in many Zanthoxylum species, and it has been reported to suppress cell proliferation, to stimulate apoptosis, to induce cell cycle arrest, and to retard migration, invasion and metastasis in a variety of malignancies via multiple molecular mechanisms (Cui et al, 2020;Nhiem et al, 2020). In this work, we unveil a potential polypharmacological capacity for nitidine, which might be responsible for its synthetic lethal activity against BRCA1-deficient cells.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…One of the key advantages of using natural products instead of synthetic compounds in drug discovery is that natural products are likely to be multi-target compounds. Nitidine is a common alkaloid found in many Zanthoxylum species, and it has been reported to suppress cell proliferation, to stimulate apoptosis, to induce cell cycle arrest, and to retard migration, invasion and metastasis in a variety of malignancies via multiple molecular mechanisms (Cui et al, 2020;Nhiem et al, 2020). In this work, we unveil a potential polypharmacological capacity for nitidine, which might be responsible for its synthetic lethal activity against BRCA1-deficient cells.…”
Section: Discussionmentioning
confidence: 88%
“…It was described to have anti-inflammatory, anti-parasitic, and antifungal properties (Nhiem et al, 2020). Interestingly, this metabolite was reported to possess potent antitumor activities by inhibiting proliferation and inducing apoptosis in several types of cancer models (Chen et al, 2012;Liao et al, 2013;Fang et al, 2013;Cui et al, 2020;Nhiem et al, 2020). Since oxynitidine is the 6-oxo analogue of nitidine, we decided to test whether nitidine also depicts selective cytotoxicity against BRCA1-deficient cells.…”
Section: The Commercially Available Alkaloid Nitidine Is a Powerful Smentioning
confidence: 99%
“…Previous studies revealed that NC has multiple pharmacological functions, such as anti-fungal, anti-inflammatory, and anti-oxidant properties 14 , 15 . Recently, several studies revealed tumor-suppressive functions of NC in various types of human malignant cancers 16 19 . As a natural anti-cancer drug, NC has received extensive attention.…”
Section: Introductionmentioning
confidence: 99%
“…Nitidine chloride (NC) has been identified as a phytochemical alkaloid that possessed antifungal, antioxidant and anticancer properties [ 6 ]. Accumulated evidence has suggested that NC exerts a tumor suppressive effect via targeting multiple signaling pathways in various human cancers [ 6 ]. NC reduced the cell migratory and invasive ability by repressing the c-Src/focal adhesion kinase (FAK) pathway in mammary carcinoma [ 7 ].…”
Section: Introductionmentioning
confidence: 99%